Technical Evaluation of Pumps in the Bio Energy Sector : Performance ,Efficiency and Sustinability Considerations - Hasith Perera; Shen Hosan; Dasith Wijesekara; Vimukthi Vithanage; Prasad Amarasingha; Niroshan Gunawardhana; Kaveenga Koswattage (MultiTech Publisher, 2024)
The bioenergy sector absolutely depends on pumps to manage fluid movement across anaerobic digestion as well as biofuel manufacturing and biomass processing activities. The research examines both efficiencies along with sustainability measures and performance qualities of bioenergy pumps by analyzing fundamental operational characteristics involving material endurance and power utilization for managing corrosive and viscous biomaterials. The research explores updated pump technology medicines positive displacement along with centrifugal pumps in order to evaluate their influence on procedure reliability and biological gas production rates and energy utilization. This analysis focuses on the comparison between standard and optimized pump solutions through a study of their whole life value and nature conservation aspects. Optimized selection of pumps combined with operational strategies will help this study make bioenergy systems more sustainable through decreased energy waste and increased process efficiency. The research presents recommendations about enhancing future designs of pumping systems and their implementation methods